2019
DOI: 10.1016/j.enbuild.2019.109358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensor position on the performance of CO2-based demand controlled ventilation

Abstract: CO2-based demand controlled ventilation (DCV) can save energy while maintaining acceptable indoor air quality. CO2 concentration may vary within an occupied space and it is unclear how sensor location influences the ventilation and energy performances. The objective of the present study is to investigate the effect of CO2 sensor position on the performance of DCV systems under mixing and displacement ventilation. Experimentally validated computational fluid dynamics (CFD) models were simulated under representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Other examples of stratification have been reported in mixing-ventilated spaces (Mahyuddin & Awbi 2010; Pei et al. 2019).
Figure 2.The concentration measured at different heights in a naturally ventilated office in London.
…”
Section: Stratificationmentioning
confidence: 72%
See 1 more Smart Citation
“…Other examples of stratification have been reported in mixing-ventilated spaces (Mahyuddin & Awbi 2010; Pei et al. 2019).
Figure 2.The concentration measured at different heights in a naturally ventilated office in London.
…”
Section: Stratificationmentioning
confidence: 72%
“…CO 2 ), which is more than sufficient to counteract the density of CO 2 at the measured concentration. Other examples of CO 2 stratification have been reported in mixing-ventilated spaces (Mahyuddin & Awbi 2010;Pei et al 2019).…”
Section: Stratificationmentioning
confidence: 79%
“…Due to the large temperature gradient between the human surface and the ambient air (>10°C), buoyancy‐driven thermal plume developed over the surface of the occupants. To simulate the turbulent flow due to this naturally convective thermal plume, Menter's shear stress transport (SST) k‐ω model was applied 32,33 . To capture detailed heat and mass transfer near the surface boundary layer, the first cell height of the human manikins was designed as 5 mm, which resulted in the average y + value (dimensionless wall distance of the cell centroid from the nearest wall) of 1.5 for the manikin surface 34 …”
Section: Methodsmentioning
confidence: 99%
“…To simulate the turbulent flow due to this naturally convective thermal plume, Menter's shear stress transport (SST) k-ω model was applied. 32,33 To capture detailed heat and mass transfer near the surface boundary layer, the first cell height of the human manikins was designed as 5 mm, which resulted in the average y + value (dimensionless wall distance of the cell centroid from the nearest wall) of 1.5 for the manikin surface. 34 The velocity field calculated from the CFD model was validated with previous measurements.…”
Section: Computational Fluid Dynamics (Cfd) Modelmentioning
confidence: 99%
“…Although CO 2 is denser than air, CO 2 stratification occurs because exhaled breath is warm, and is either immediately entrained into the main body plume or rises as a secondary plume where it typically settles at an intermediate height before being entrained and carried into the upper layer (Bhagat et al, 2020). Pei et al (2019) showed that temperature and CO 2 The objective was to sample the building and its typical contents to capture the combined effect of the following Furniture and numerous architectural models and model making equipment were present throughout the space…”
Section: Co 2 Monitoring Scenarios and Objectivesmentioning
confidence: 99%